Reporting assurance for religious compliance in Islamic banks: are we there yet? - Sheikh Hassan, Ahmad Fahmi; Mohd Haridan, Nurfarahin; Mohd Zamil, Nor Aiza; Muhammad, Junaina (Serials Publications, 2015)
Shariah boards (SBs) play a unique role by providing assurance on religious compliance of Islamic banks. In fulfilling this governance responsibility, SB members must exercise diligence, independence and be transparent at all times. In this study, we examine the distinct governance structure of Malaysian Islamic banks as the country is perceived to have the most developed governance framework in the Islamic world. We critically evaluate the literature on the role and function of SBs and assess the existing support mechanisms available and identify challenges in providing effective religious compliance reviews. We highlight the inherent limitations of Malaysian SBs in performing the compliance review with studies reporting the independence of this authority being compromised with SBs appearing to rubber-stamp decisions already taken by top management. Finally, we highlight serious concern regarding the quality of the religious assurance provided in annual reports of Islamic banks and question as to who holds the ultimate right to provide the all-importantreligious assurance for the Islamic finance industry?